(untitled) (Journal of Informatics Education and Research, 2025)
The Insolvency and Bankruptcy Code (IBC), 2016, is a major change to India’s financial and legal systems. Its goal is to speed up the resolution of stressed assets and make the banking sector more stable. This study analyses the effect of IBC implementation on the management of non-performing assets (NPAs) at the State Bank of India (SBI), utilising secondary data from the pre-IBC period (2010–2016) and the post-IBC period (2017–2024). Utilising a comprehensive quantitative methodology—comprising descriptive statistics, trend analysis, comparative pre- and post-IBC evaluation, interrupted time-series (ITS) regression, ARIMA forecasting, and the decomposition of NPA drivers—the study examines structural transformations in asset quality and recovery efficiency. Results show that both gross and net NPAs went down a lot after the IBC. This was also true for provisioning coverage and recovery rates. ITS regression and ARIMA analyses validate that these enhancements are statistically significant and enduring, whereas decomposition analysis indicates that improved recovery mechanisms and policy-driven interventions were the principal factors in the reduction of NPAs. Robustness checks, encompassing alternative dependent variables and sub-period analyses, affirm the reliability of the findings. Even though the study has some flaws, like relying on secondary data and only looking at one bank, it shows that IBC has made SBI’s NPA management framework much stronger and gives ideas for how to use it in other parts of the Indian banking sector. The results show how important institutional reforms, effective law enforcement, and strategic monitoring are for improving financial stability and getting rid of stressed assets.